Enzalutamide-containing tablet
By formulating enzalutamide-containing tablets with a solid dispersion of specific polymers and alphalated starch, the tablets exhibit enhanced dissolution and supersaturation properties, addressing the suboptimal dissolution issues in existing formulations and improving the efficacy of prostate cancer treatment.
Patent Information
- Application Number
- JP2024185445
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-02
- Filing Date
- 2024-10-02
- Publication Date
- 2025-04-14
Smart Images

Figure 2025062591000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an enzalutamide-containing tablet that exhibits good dissolution properties. [Background technology]
[0002] Enzalutamide has the chemical name 4-{3-[4-Cyano-3-(trifluoromethyl)phenyl]-5,5-dimethyl-4-oxo-2-sulfanylideneimidazolidin-1-yl}-2-fluoro-N-methylbenzamide, and tablets containing enzalutamide as the active ingredient are known to be a prostate cancer treatment and are sold as XTANDI tablets (Non-Patent Document 1).
[0003] Patent Document 1 describes an invention relating to a solid formulation with excellent solubility and absorption, which contains amorphous enzalutamide and a polymer consisting of hydroxypropyl methylcellulose, hydroxypropyl methylcellulose phthalate, or hydroxypropyl methylcellulose acetate succinate.
[0004] Patent document 2 describes an invention relating to a solid formulation containing enzalutamide and polyvinyl alcohol with a degree of saponification of 30 mol% or more and less than 85 mol%, which has improved solubility and / or dissolution properties and excellent ability to maintain supersaturation. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6404217 [Patent Document 2] Patent No. 7172997 [Non-patent literature]
[0006] [Non-Patent Document 1] Package insert "XTANDI Tablets 40mg / 80mg", May 2020 (1st edition) Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an enzalutamide-containing tablet that exhibits good dissolution properties. [Means for solving the problem]
[0008] The inventors of the present invention have discovered that by including a solid dispersion containing enzalutamide and a specific polymer in a tablet containing enzalutamide, it is possible to provide a tablet containing enzalutamide having good dissolution properties, and have thus completed the present invention.
[0009] That is, the present invention provides (1) A tablet comprising a solid dispersion containing enzalutamide and one or more polymers selected from the group consisting of copolyvidone, methacrylic acid copolymer, methylcellulose, and polyvinyl alcohol; (2) The tablet according to (1) above, wherein the polymer is a copolyvidone and methacrylic acid copolymer. (3) The tablet according to (1) above, wherein the polymer is copolyvidone and methylcellulose. (4) The tablet according to (1) above, wherein the polymer is copolyvidone and polyvinyl alcohol. (5) The tablet according to any one of (1) to (4), wherein the blending ratio of the polymer is 10.0 to 80.0% by weight based on the total weight of the tablet. (6) The tablet according to any one of (1) to (4), wherein the blending ratio of the polymer is 1:0.1 to 1:20, where the blending amount of the enzalutamide is 1. (7) The tablet according to (1), further comprising pregelatinized starch. (8) The tablet according to (7), wherein the blending ratio of pregelatinized starch is 0.1 to 50.0% by weight based on the total weight of the tablet. (9) The tablet according to (1), which is an orally disintegrating tablet. (10) The tablet according to (1), wherein the tablet is a film-coated tablet. (11) A method for producing a tablet comprising a solid dispersion containing enzalutamide and one or more polymers selected from the group consisting of copolyvidone, methacrylic acid copolymer, methylcellulose, and polyvinyl alcohol; This is regarding. Effect of the Invention
[0010] According to the present invention, by forming a tablet containing a solid dispersion containing enzalutamide and two or more specific polymers, and further by containing pregelatinized starch in the tablet, it is possible to provide a tablet exhibiting good dissolution properties. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 shows powder X-ray diffraction patterns of the solid dispersions and enzalutamide bulk produced in Production Examples 1 to 9. [Diagram 2] 1 shows the measurement results of dissolution tests of SD1 to 3 (solid dispersions) produced in Production Examples 1 to 3, and tablets 1 and 2 produced in Examples 1 and 2. [Diagram 3] 1 shows the measurement results of dissolution tests of SD2 (solid dispersion) and SD4 (solid dispersion) produced in Production Example 2 and Production Example 4, and tablet 3 produced in Example 3. [Figure 4] 1 shows the results of dissolution test of SD2 (solid dispersion) and SD5 (solid dispersion) produced in Production Example 2 and Production Example 5, and Tablet 4 produced in Example 4. [Diagram 5] 1 shows the results of an investigation of the test liquid in a dissolution test using tablet 1 produced in Example 1. [Figure 6] These are powder X-ray diffraction patterns of SD6 (solid dispersion) produced in Production Example 6 at the start of storage and after 1, 2, and 6 weeks of storage at 40°C and a relative humidity of 75%, and of the enzalutamide drug substance. [Figure 7]1 shows the measurement results of the dissolution test of tablets 5 to 7 produced in Examples 5 to 7. [Figure 8] 1 shows powder X-ray diffraction patterns of SD10 (solid dispersion), SD11 (solid dispersion), and enzalutamide drug substance (ENZ) produced in Production Examples 10 and 11. [Figure 9] 1 shows the measurement results of the dissolution test of tablets 8 and 9 produced in Examples 8 and 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this specification, the term "solid dispersion" refers to a matrix in which a drug and a polymer are mixed, solidified, and the amorphous drug is stably dispersed in the polymer. In detail, the solid dispersion refers to a matrix in which a drug and a water-soluble polymer are dissolved and mixed in a solvent, solidified, and the amorphous drug is stably dispersed in the polymer. It means a formulation technology that makes a crystalline poorly soluble drug into a solid dispersion, thereby making the drug amorphous and improving the solubility and dissolution rate. Examples of methods for producing a solid dispersion include a spray drying method, an evaporation method, a heated melt kneading extrusion method, and a mixed grinding method.
[0013] The term "spray drying method" as used herein refers to a method for producing a solid dispersion by dissolving or suspending a drug and a polymer, and optionally a pharma- ceutically acceptable additive, in a solvent (an organic solvent, water, or a mixture thereof), and then spraying the solvent into a mist using a spray dryer or the like while simultaneously drying the solution instantaneously.
[0014] The "evaporation method" in this specification means a method in which a drug and a polymer, and optionally a pharma- ceutically acceptable additive, are dissolved or suspended in a solvent (an organic solvent, water, or a mixture thereof), and then the solvent is removed using a rotary evaporator or the like to precipitate a solid dispersion, or a solid dispersion is precipitated in the solvent.
[0015] In this specification, the term "heated melt-kneading extrusion method" refers to a method of producing a solid dispersion by melt-kneading a drug, a polymer, and optionally a pharma- ceutically acceptable additive, and cooling the mixture. The mixing temperature during melt-kneading may be any temperature at which the drug and the polymer dissolve. In one embodiment, the temperature is 80°C to 300°C, in another embodiment, 90°C to 250°C, and in another embodiment, 100°C to 200°C.
[0016] The term "mixing and grinding method" as used herein means a method in which a drug and a polymer, and optionally a pharma- ceutically acceptable additive, are mixed together, and then a solid dispersion is produced using a mixer and grinder such as a ball mill or a hammer mill.
[0017] In the present specification, "amorphous" refers to a substantially amorphous state, and means a state that does not have a regular three-dimensional crystal structure. For example, it means that 80% or more, 90% or more, 95% or more, and 99% or more of the compounds present in the composition are in an amorphous form in some embodiments. In addition, the crystallinity means, for example, about 20% or less crystallinity in some embodiments, about 10% or less crystallinity in some embodiments, about 5% or less crystallinity in some embodiments, and about 1% or less crystallinity in some embodiments. Whether the compound or formulation is amorphous can be measured by several techniques, including, for example, powder X-ray diffraction, Raman spectroscopy, infrared spectroscopy, differential scanning calorimetry, solid-state NMR, and electron microscopy.
[0018] As used herein, "amorphous stability" means that the solid dispersion is capable of suppressing crystallization of the amorphous compound in a stability test over time.
[0019] In the present specification, "improving dissolution" means improving the dissolution rate of enzalutamide from a tablet. Specifically, for example, the average dissolution rate at 90 minutes after the start of the test is defined as 50% or more in one embodiment, and 60% or more in another embodiment.
[0020] In this specification, "D90" refers to the volumetric particle size measured by a laser diffraction method. In principle, it means the particle size at the time when particles of a certain volume are sieved in ascending order of size and the particles that make up 90% of the volume are separated.
[0021] In this specification, "D50 (average particle size)" refers to the particle size based on volume measured by laser diffraction. In principle, it means the particle size at the time when particles of a certain volume are sieved in ascending order of size and the particles that make up 50% of the volume are separated.
[0022] In this specification, "D10" refers to the volumetric particle size measured by a laser diffraction method. In principle, it means the particle size at the time when particles of a certain volume are sieved in ascending order of size and the particles corresponding to 10% of the volume are separated.
[0023] The manufacturing method of the enzalutamide-containing tablet of the present invention is described below.
[0024] Enzalutamide used in the present invention is manufactured according to the method described in Japanese Patent No. 5718372.
[0025] The drug's indications are "castration-resistant prostate cancer" and "prostate cancer with distant metastasis," and its dosage is "adults are usually given 160 mg of enzalutamide orally once a day."
[0026] The amount of enzalutamide is not particularly limited as long as it is the amount of enzalutamide in the formulation that constitutes the dosage as a pharmaceutical formulation. For example, it is 1 to 50% by weight in one embodiment, 2 to 40% by weight in one embodiment, and 5 to 20% by weight in one embodiment, based on the total weight of one tablet. Also, for example, it is 2 to 30% by weight in one embodiment, and 6 to 18% by weight in one embodiment, based on the uncoated tablet portion of one tablet.
[0027] From the viewpoint of manufacturability, the D90 of enzalutamide is in one embodiment 10 μm or more and 500 μm or less, in one embodiment 20 μm or more and 400 μm or less, and in one embodiment 30 μm or more and 300 μm or less.
[0028] From the viewpoint of manufacturability, the D50 of enzalutamide is in one embodiment 1 μm or more and 500 μm or less, in one embodiment 10 μm or more and 200 μm or less, and in one embodiment 20 μm or more and 100 μm or less.
[0029] From the viewpoint of manufacturability, the D10 of enzalutamide is in one embodiment 0.1 μm or more and 200 μm or less, in one embodiment 0.2 μm or more and 100 μm or less, and in one embodiment 0.5 μm or more and 50 μm or less.
[0030] The polymer used in the solid dispersion of the present invention is not particularly limited as long as it is pharmaceutically acceptable, does not affect the stability of the active ingredient, or has little effect, and supports enzalutamide as an amorphous substance, and may be a mixture of two or more kinds. Specifically, it is, for example, a water-soluble polymer. The water-soluble polymer may be any one that can be used pharmaceutical preparations, specifically, cellulose-based polymers, vinyl-based polymers, acrylic acid-based polymers, and polyether-based polymers. Preferred are cellulose-based polymers, vinyl-based polymers, and acrylic acid-based polymers.
[0031] Specific examples of cellulose-based polymers include hydroxypropyl cellulose, hypromellose, hydroxypropyl methylcellulose phthalate, methylcellulose, carboxymethylethyl cellulose, hydroxypropyl methylcellulose acetate succinate, hydroxyethyl methylcellulose, hydroxyethyl cellulose, carmellose sodium, carmellose calcium, and cellulose acetate phthalate.
[0032] Specific examples of vinyl polymers include polyvinyl polypyrrolidone, polyvinyl alcohol, copolyvidone, polyvinyl alcohol-acrylic acid-methyl methacrylate copolymer, and the like.
[0033] Specific examples of acrylic acid-based polymers include aminoalkyl methacrylate copolymer E, methacrylic acid copolymer (methacrylic acid copolymer L, methacrylic acid copolymer LD, methacrylic acid copolymer S), aminoalkyl methacrylate copolymer RS, ethyl acrylate-methyl methacrylate copolymer, ammonia alkyl methacrylate copolymer, methyl acrylate-methacrylic acid-methyl methacrylate copolymer, 2-methyl-5-vinylpyridine methylacrylate-methacrylic acid copolymer, and the like.
[0034] The water-soluble polymer used in the present invention also functions as a pharmaceutical additive, such as a vehicle, binder, disintegrant, lubricant, or coating agent.
[0035] Specific examples of copolyvidone include Kollidon (registered trademark) VA64, Kollidon (registered trademark) VA64 Fine (manufactured by BASE Japan), Plasdon S-630, Plasdon S-630 Ultra (manufactured by Ashland Japan), and Copolyvidone (manufactured by MP Gokyo Food & Chemical).
[0036] Specific examples of methacrylic acid copolymers LD include EUDRAGIT (registered trademark) L100-55, EUDRAGIT (registered trademark) L30D-55 (manufactured by EVONIK), Kollicoat (registered trademark) MAE30DP (manufactured by BASF Japan), Polyquid (registered trademark) PA-30, and Polyquid (registered trademark) PA-30S (manufactured by Sanyo Chemical Industries, Ltd.).
[0037] Specific examples of methacrylic acid copolymer L include EUDRAGIT (registered trademark) L100, EUDRAGIT (registered trademark) L12.5, EUDRAGIT (registered trademark) S12.5 (manufactured by EVONIK), and POLYQUID (registered trademark) LA-100 (manufactured by Sanyo Chemical Industries, Ltd.).
[0038] A specific example of the methacrylic acid copolymer S is EUDRAGIT (registered trademark) S100 (manufactured by EVONIK).
[0039] Specific examples of hydroxypropyl cellulose include HPC-H, HPC-M, HPC-L, HPC-SL, HPC-SSL (manufactured by Nippon Soda), Klucel(H), Klucel(M), Klucel(G), Klucel(J), Klucel(L), and Klucel(E) (manufactured by Ashland Japan).
[0040] Specific examples of methylcellulose include METOLOSE (registered trademark) SM-4, METOLOSE (registered trademark) SM-4VF, METOLOSE (registered trademark) SM-15, METOLOSE (registered trademark) SM-25, METOLOSE (registered trademark) SM-100, METOLOSE (registered trademark) SM-400, METOLOSE (registered trademark) SM-1500, and METOLOSE (registered trademark) SM-4000 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0041] Specific examples of polyvinyl alcohol include PE-05JPS (manufactured by Japan Vinyl Acetate & Poval), GOHSENOL (registered trademark) EG-03P, GOHSENOL (registered trademark) EG-05P, GOHSENOL (registered trademark) EG-18P, GOHSENOL (registered trademark) EG-22P, GOHSENOL (registered trademark) EG-30P, GOHSENOL (registered trademark) EG-40P, GOHSENOL (registered trademark) EG-48P, GOHSENOL (registered trademark) EG-05PW, GOHSENOL (registered trademark) EG-30PW, and GOHSENOL (registered trademark) EG-40PW (manufactured by Mitsubishi Chemical).
[0042] The amount of the polymer is not particularly limited as long as it is an amount that can achieve good dissolution of enzalutamide. For example, the amount is 10.0 to 80.0% by weight in one embodiment, 15.0 to 70.0% by weight in one embodiment, and 20.0 to 60.0% by weight in one embodiment, based on the total amount of the tablet. In addition, for example, when the amount of enzalutamide is 1, the ratio of enzalutamide to polymer is 1:0.1 to 1:20 in one embodiment, 1:0.5 to 1:10 in one embodiment, 1:1 to 1:8 in one embodiment, and 1:2 to 1:6 in one embodiment.
[0043] The pregelatinized starch used in the present invention is not particularly limited as long as it is pharma- ceutical acceptable and does not affect the stability of the active ingredient or has only a small effect on it.Specific examples include Matsunolin (registered trademark) SM (manufactured by Matsutani Chemical Industry Co., Ltd.), SWELSTAR MX-1, SWELSTAR PD-1, SWELSTAR WB-1 (manufactured by Asahi Kasei Co., Ltd.), Amycol (registered trademark) C, Amycol (registered trademark) HF (manufactured by Nippon Starch Chemical Co., Ltd.), and Prejel PA5 PH (manufactured by DFE Pharma Co., Ltd.).
[0044] The amount of pregelatinized starch is not particularly limited as long as it is an amount that can achieve good dissolution of enzalutamide. Specifically, for example, it is 3.0 to 50.0% by weight in one embodiment, 5.0 to 40.0% by weight in one embodiment, and 10.0 to 30.0% by weight in one embodiment based on the total weight of the tablet. When the amount of enzalutamide is 1, the ratio of enzalutamide: pregelatinized starch is 1:0.1 to 1:10 in one embodiment, 1:0.5 to 1:5 in one embodiment, and 1:1 to 1:2.5 in one embodiment.
[0045] The tablet of the present invention may contain pharmaceutical additives as necessary, such as excipients, binders, disintegrants, lubricants, surfactants, flow agents, coating agents, acidulants, effervescent agents, sweeteners, flavors, colorants, buffers, and antioxidants.
[0046] Examples of excipients include D-mannitol, corn starch, crystalline cellulose, trehalose, anhydrous calcium hydrogen phosphate, D-sorbitol, maltitol, xylitol, lactose, sucrose, sodium carmellose, synthetic aluminum silicate, magnesium aluminometasilicate, sucrose fatty acid esters, precipitated calcium carbonate, maltose hydrate, calcium hydrogen phosphate, gum arabic, dextrin, and pullulan.
[0047] Examples of binders include hypromellose, polyvinylpyrrolidone, polyvinyl alcohol-polyethylene glycol graft copolymer, polyvinyl alcohol-acrylic acid-methyl methacrylate copolymer, hydroxyethylcellulose, glyceryl monostearate, macrogol 6000, and polyoxyl 40 stearate.
[0048] Examples of disintegrants include corn starch, potato starch, sodium starch glycolate, carmellose, carmellose calcium, hydroxypropyl starch, croscarmellose, croscarmellose sodium, and crospovidone.
[0049] Examples of lubricants include stearic acid, magnesium stearate, sodium stearate, calcium stearate, talc, sodium stearyl fumarate, hardened oil, and sucrose fatty acid esters.
[0050] Examples of the surfactant include polysorbate 80, sodium lauryl sulfate, polyoxyethylene hydrogenated castor oil, and the like.
[0051] Examples of the fluidizing agent include light anhydrous silicic acid, hydrous silicon dioxide, magnesium aluminometasilicate, and talc.
[0052] Examples of coating agents include hypromellose, polyvinyl alcohol-polyethylene glycol graft copolymer, polyvinyl alcohol-acrylic acid-methyl methacrylate copolymer, polyethylene glycol, glycerin monostearate, titanium oxide, and talc.
[0053] Examples of acidulants include citric acid, tartaric acid, malic acid, etc.
[0054] The foaming agent may, for example, be sodium bicarbonate.
[0055] Examples of sweeteners include sucralose, sodium saccharin, dipotassium glycyrrhizinate, aspartame, stevia, and thaumatin.
[0056] Examples of the flavoring include lemon, lemon-lime, orange, and menthol.
[0057] Examples of coloring agents include ferric oxide, yellow ferric oxide, black ferric oxide, titanium oxide, Food Yellow No. 4, Food Yellow No. 5, Food Red No. 3, Food Red No. 102, Food Blue No. 3, and the like.
[0058] Examples of buffering agents include citric acid, succinic acid, fumaric acid, tartaric acid, ascorbic acid or a salt thereof, glutamic acid, glutamine, glycine, aspartic acid, alanine, arginine or a salt thereof, magnesium oxide, zinc oxide, magnesium hydroxide, phosphoric acid, boric acid or a salt thereof, and the like.
[0059] Examples of the antioxidant include ascorbic acid, dibutylhydroxytoluene, and propyl gallate.
[0060] In the tablet of the present invention, various further pharmaceutical additives may be appropriately used within the range in which the desired effects of the present invention are achieved.
[0061] The various additional pharmaceutical additives contained in the tablet of the present invention can be appropriately combined.
[0062] The blending amount is not particularly limited as long as it does not affect the achievement of the desired effects of the present invention.
[0063] The method for producing the solid dispersion of the present invention may be any method as long as it can achieve the object of the present invention. For example, in one embodiment, enzalutamide and a polymer, and optionally a pharma- ceutical acceptable additive are dissolved in a solvent (organic solvent, water, or a mixture thereof), and the solvent is sprayed in a mist form using a spray dryer and / or a fluidized bed granulator, and simultaneously, instantaneously dried, etc. can be produced. In another embodiment, enzalutamide and a polymer, and optionally a pharma- ceutical acceptable additive are dissolved in a solvent (organic solvent, water, or a mixture thereof), and the solvent is distilled off using a rotary evaporator, etc. can be produced. In another embodiment, enzalutamide and a polymer, and optionally a pharma- ceutical acceptable additive are melt-kneaded, and the mixture is cooled, etc. can be produced.
[0064] The manufacturing method for tablets containing a solid dispersion may be any manufacturing method as long as it can achieve the object of the present invention. For example, in one embodiment, a pharma- ceutically acceptable additive may be added to the solid dispersion, and tablets may be manufactured by direct tableting. In another embodiment, a pharmaceutical additive may be added to the solid dispersion, granulated, and tablets may be manufactured using a tablet press. In addition, during tableting, tablets may be compressed while spraying a lubricant using an external lubricating device. Furthermore, if necessary, a film-coating liquid may be sprayed on the tablet, followed by drying to manufacture a film-coated tablet.
[0065] The tablet of the present invention may be packaged using various pharmaceutical packaging materials. EXAMPLES
[0066] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.
[0067] <Production Example 1> Preparation of solid dispersion by spray drying, Enzalutamide:Copolyvidone=1:2 A solution of 3.33 g of enzalutamide and 6.67 g of copolyvidone (Kollidon (registered trademark) VA64, manufactured by BASF Japan) dissolved in 90 g of methanol was filtered through a sieve with an opening of 100 μm and spray-dried using a spray dryer (Mini spray dryer B-290, manufactured by Nippon Buchi Co., Ltd.) to obtain a solid dispersion SD1.
[0068] <Production Example 2> Preparation of solid dispersion by spray drying, Enzalutamide:Copolyvidone=1:4 A solution of 2.0 g of enzalutamide and 8.0 g of copolyvidone (Kollidon (registered trademark) VA64, manufactured by BASF Japan) dissolved in 90 g of methanol was filtered through a sieve with an opening of 100 μm and spray-dried using a spray dryer (Mini spray dryer B-290, manufactured by Nippon Buchi Co., Ltd.) to obtain a solid dispersion SD2.
[0069] <Production Example 3> Preparation of solid dispersion by spray drying method, Enzalutamide: methacrylic acid copolymer LD = 1:2 A solution of 3.33 g of enzalutamide and 6.67 g of methacrylic acid copolymer LD (Eudragit (registered trademark) L100-55, manufactured by EVONIK Nutrition & Care GmbH) dissolved in 90 g of methanol was filtered through a sieve with an opening of 100 μm and spray-dried using a spray dryer (Mini spray dryer B-290, manufactured by Nippon Buchi Co., Ltd.) to obtain a solid dispersion SD3.
[0070] <Production Example 4> Preparation of solid dispersion by spray drying method, Enzalutamide:Methylcellulose=1:4 A solution of 2.0 g of enzalutamide and 8.0 g of methylcellulose (METOLOSE (registered trademark) SM-4, manufactured by Shin-Etsu Chemical Co., Ltd.) dissolved in 90 g of a mixture of acetone / water = 7:3 was filtered through a sieve with an opening of 100 μm and spray-dried using a spray dryer (Mini spray dryer B-290, manufactured by Nippon Buchi Co., Ltd.) to obtain a solid dispersion SD4.
[0071] <Production Example 5> Preparation of solid dispersion by spray drying method, Enzalutamide: polyvinyl alcohol = 1:4 A solution of 1.0 g of enzalutamide and 4.0 g of polyvinyl alcohol (PE-05JPS (saponification degree 88 mol%) manufactured by Nippon Vinyl Acetate & Poval) dissolved in 90 g of a mixture of methanol / water = 76:24 was filtered through a sieve with 100 μm openings and spray-dried using a spray dryer (Mini spray dryer B-290 manufactured by Nippon Buchi Co., Ltd.) to obtain solid dispersion SD5.
[0072] Table 1 shows the production conditions for SD1 to SD5 produced in Production Examples 1 to 5.
[0073] [Table 1]
[0074] <Production Example 6> Preparation of solid dispersion by solvent distillation method, Enzalutamide: methacrylic acid copolymer LD: copolyvidone = 1:2:2 1.0 g of enzalutamide, 2.0 g of methacrylic acid copolymer LD (Eudragit (registered trademark) L100-55, manufactured by EVONIK Nutrition & Care GmbH), and 2.0 g of copolyvidone (Kollidon (registered trademark) VA64, manufactured by BASF Japan) were placed in a round-bottom flask, and 200 g of methanol was added to dissolve the solution. The solvent was then removed using a rotary vacuum evaporator (Tokyo Rika Kikaisha; N-1000 type), and the solids were scraped off from the round-bottom flask and pulverized in an agate mortar to obtain solid dispersion SD6.
[0075] <Production Example 7> Preparation of solid dispersion by solvent distillation method, Enzalutamide: methacrylic acid copolymer LD: hydroxypropyl cellulose = 1:2:2 1.0 g of enzalutamide, 2.0 g of methacrylic acid copolymer LD (Eudragit (registered trademark) L100-55, manufactured by EVONIK Nutrition & Care GmbH), and 2.0 g of hydroxypropyl cellulose (HPC-L, manufactured by Nippon Soda Co., Ltd.) were placed in a round-bottom flask, and 200 g of methanol was added to dissolve the solution. The solvent was then removed using a rotary vacuum evaporator (N-1000 model, manufactured by Tokyo Rikakikai Co., Ltd.), and the solids were scraped off from the round-bottom flask and pulverized in an agate mortar to obtain solid dispersion SD7.
[0076] The production conditions for SD6 to SD7 produced in Production Examples 6 to 7 are shown in Table 2.
[0077] [Table 2]
[0078] <Production Example 8> Preparation of solid dispersion by hot melt kneading extrusion method, Enzalutamide: methylcellulose: copolyvidone = 1:2:2 1.4 g of enzalutamide, 2.8 g of methylcellulose (METOLOSE (registered trademark) SM-4, manufactured by Shin-Etsu Chemical Co., Ltd.), and 2.8 g of copolyvidone (Kollidon (registered trademark) VA64, manufactured by BASF Japan) were mixed in a mortar, and the mixture was filled into a microcompounder (HAAKE MiniLabII, manufactured by Thermo Fisher Scientific), melt-kneaded at 190°C for 10 minutes, cooled, and then pulverized using a pulverizer (Wonder Crusher WC-3, manufactured by Osaka Chemical Co., Ltd.) to obtain a solid dispersion SD8.
[0079] <Production Example 9> Preparation of solid dispersion by hot melt kneading extrusion method, Enzalutamide: Polyvinyl alcohol: Copolyvidone = 1:2:2 1.4 g of enzalutamide, 2.8 g of polyvinyl alcohol (manufactured by Japan Vinyl Acetate & Poval: PE-05JPS (saponification degree 88 mol%)), and 2.8 g of copolyvidone (manufactured by BASF Japan: Kollidon (registered trademark) VA64) were mixed in a mortar, and the mixture was charged into a microcompounder (manufactured by Thermo Fisher Scientific; HAAKE MiniLabII), melt-kneaded at 190°C for 10 minutes, cooled, and then pulverized using a pulverizer (manufactured by Osaka Chemical; Wonder Crusher WC-3) to obtain a solid dispersion SD9.
[0080] Table 3 shows the production conditions for SD8 to SD9 produced in Production Examples 8 to 9.
[0081] [Table 3]
[0082] <Test Example 1: Evaluation of crystal form after preparation of solid dispersion> The crystal state of the solid dispersions SD1 to 9 and the amorphous enzalutamide drug substance obtained from Preparation Examples 1 to 9 was confirmed by powder X-ray diffraction measurement. For the measurement, a powder X-ray diffraction device Smart Lab 3kW (manufactured by Rigaku) was used, and the measurement was performed under the following conditions: measurement method: reflection method, filter: Cu K-bate, X-ray output: 40kV, 30mA, measurement range: 2θ=3 to 40deg, scan speed: 8deg / min, step width: 0.02deg. The evaluation results of the crystal state are shown in Table 4 and Figure 1.
[0083] [Table 4]
[0084] A halo pattern was observed in all of the solid dispersions SD1 to 9 obtained in Production Examples 1 to 9, indicating that the enzalutamide in the solid dispersions had formed an amorphous state after preparation.
[0085] <Examples 1 to 4> Preparation of tablets 1 to 4 Crystalline cellulose (Asahi Kasei: Ceolas (registered trademark) UF-702) 13.48 g, light anhydrous silicic acid (Freund Sangyo: Adsolider (registered trademark) 101) 0.17 g, croscarmellose sodium (DuPont: Ac-Di-Sol (registered trademark) SD-711) 2.68 g, magnesium stearate (Taihei Chemical Industry: magnesium stearate (vegetable)) 0.17 g were mixed to prepare an additive mixture. Enzalutamide 40 mg equivalent (0.20 g) in the solid dispersions SD6 to 9 obtained in Production Examples 6 to 9, and 0.165 g of the additive mixture were weighed out, mixed in a φ9.5 mm mortar, and tableted using a hand press machine at 1 kN to obtain circular plain tablets (tablets 1 to 4) with a tablet mass of 365 mg and φ9.5 mm.
[0086] The formulations of tablets 1 to 4 produced in Examples 1 to 4 are shown in Table 5.
[0087] [Table 5]
[0088] <Test Example 2: Examination of combination of solid dispersions and blending amount of copolyvidone> Dissolution tests were performed on SD1-3 and tablets 1-2 according to the Japanese Pharmacopoeia Dissolution Test Method, 18th Edition. Dissolution of the tablets was performed using a paddle method in a dissolution tester (manufactured by Toyama Sangyo Co., Ltd.), with the test liquid being 900 mL of dissolution test second liquid (pH 6.8) and the paddle rotation speed being 50 rpm. Regarding the test specimens, in the case of SD1-3, 0.165 g of the additive mixture prepared in Examples 1-4 was added, and then a solid dispersion equivalent to 40 mg of enzalutamide was added, and in the case of tablets 1-2, one tablet was added and the test was performed. 15 mL of the dissolution liquid was withdrawn over time from the start of the test until 180 minutes, and immediately 15 mL of the test liquid heated to 37±0.5°C was accurately replenished. The dissolution liquid was filtered through a membrane filter with a pore size of 0.45 μm or less, and the dissolution rate of the filtrate was calculated by liquid chromatography. The ultraviolet absorbance of enzalutamide was measured at 237 nm. The test results are shown in Table 6 and Figure 2.
[0089] [Table 6]
[0090] For Test Example 2, the ratio of enzalutamide:polymer=1:2 or enzalutamide:polymer=1:4 was examined. SD1 (enzalutamide:copolyvidone=1:2) consisting of copolyvidone alone had a slow dissolution rate. SD3 (enzalutamide:methacrylic acid copolymer LD=1:2) consisting of methacrylic acid copolymer LD alone showed a fast initial dissolution rate but showed a decrease in dissolution rate after 30 minutes, and had a low ability to maintain supersaturation. SD2 (enzalutamide:copolyvidone=1:4), which was obtained by increasing the amount of copolyvidone from SD1 (enzalutamide:copolyvidone=1:2), showed a higher dissolution rate than SD1 (enzalutamide:copolyvidone=1:2), but had a slower dissolution rate than SD3 (enzalutamide:methacrylic acid copolymer LD=1:2). Tablet 1 (Enzalutamide: Methacrylic acid copolymer LD: Copolyvidone = 1:2:2), which uses two types of polymers, copolyvidone and methacrylic acid copolymer LD (weight ratio of copolyvidone: methacrylic acid copolymer LD = 1:1), in the same weight ratio of enzalutamide: polymer = 1:4 as SD2 (Enzalutamide: Copolyvidone = 1:4), had a fast initial dissolution rate and maintained a dissolution rate of 80% or more even after 3 hours, demonstrating good supersaturation maintenance ability. Tablet 2 (Enzalutamide: Methacrylic acid copolymer LD: Hydroxypropylcellulose = 1:2:2), which replaced the copolyvidone in tablet 1 (Enzalutamide: Methacrylic acid copolymer LD: Copolyvidone = 1:2:2) with hydroxypropylcellulose, showed an improvement in the initial dissolution rate, but had poor supersaturation maintenance ability, and the dissolution rate after 60 minutes decreased.
[0091] <Test Example 3: Study on the combination of copolyvidone and methylcellulose> Dissolution tests were performed on SD2 (enzalutamide:copolyvidone=1:4), SD4 (enzalutamide:methylcellulose=1:4), and tablet 3 (enzalutamide:methylcellulose:copolyvidone=1:2:2) under the same test conditions as in Test Example 2, and the dissolution rates were calculated. The test results are shown in Table 7 and Figure 3.
[0092] [Table 7]
[0093] For Test Example 3, enzalutamide:polymer = 1:4 was used. SD2 (enzalutamide:copolyvidone = 1:4) consisting of copolyvidone alone and SD4 (enzalutamide:methylcellulose = 1:4) consisting of methylcellulose alone showed good supersaturation maintenance ability, but the dissolution rate was low. SD2 (enzalutamide:copolyvidone = 1:4) also showed a slow dissolution rate. Tablet 3 (enzalutamide:methylcellulose:copolyvidone = 1:2:2), which contains equal amounts of copolyvidone and methylcellulose, showed an improvement in the maximum dissolution rate.
[0094] <Test Example 4: Study on the combination of copolyvidone and polyvinyl alcohol> Dissolution tests were performed on SD2 (enzalutamide:copolyvidone=1:4), SD5 (enzalutamide:polyvinyl alcohol=1:4), and tablet 4 (enzalutamide:polyvinyl alcohol:copolyvidone=1:2:2) under the same test conditions as in Test Example 2, and the dissolution rates were calculated. The test results are shown in Table 8 and FIG.
[0095] [Table 8]
[0096] For Test Example 4, enzalutamide:polymer=1:4 was used. SD2 (enzalutamide:copolyvidone=1:4) consisting of copolyvidone alone had good supersaturation maintenance ability but slow dissolution rate. SD5 (enzalutamide:polyvinyl alcohol=1:4) consisting of polyvinyl alcohol alone showed fast initial dissolution but poor supersaturation maintenance ability, and the dissolution rate after 30 minutes decreased. At a weight ratio of enzalutamide:polymer=1:4, tablet 4 (enzalutamide:polyvinyl alcohol:copolyvidone=1:2:2) using two types of polymer, copolyvidone and polyvinyl alcohol (weight ratio of copolyvidone:polyvinyl alcohol=1:1), showed slower initial dissolution rate than SD5 (enzalutamide:polyvinyl alcohol=1:4), but had good supersaturation maintenance ability and maintained a dissolution rate of 80% or more even after 3 hours.
[0097] <Test Example 5: Study of dissolution test medium> A dissolution test was conducted on tablet 1 (enzalutamide: methacrylic acid copolymer LD: copolyvidone = 1:2:2) according to the 18th revised Japanese Pharmacopoeia dissolution test method. The dissolution of the tablet was performed by the paddle method in a dissolution tester (manufactured by Toyama Sangyo) with 900 mL of each test solution and a paddle rotation speed of 50 rpm, and two tablets were placed in the solution. The test solutions were "Dissolution test second solution (pH 6.8)", "Dissolution test second solution (pH 6.8) + hydroxypropyl cellulose (manufactured by Nippon Soda: HPC-L) 160 mg", and "Dissolution test second solution (pH 6.8) + pregelatinized starch (manufactured by Matsutani Chemical Industry: Matsunolin (registered trademark) SM) 160 mg added" from the start of the test until 180 minutes later, and 15 mL of the test solution heated to 37 ± 0.5 ° C was accurately added. The eluate was filtered through a membrane filter with a pore size of 0.45 μm or less, and the elution rate of the filtrate was calculated by liquid chromatography. The ultraviolet absorbance of Enzalutamide was measured at 237 nm. The test results are shown in Table 9 and Figure 5.
[0098] [Table 9]
[0099] In systems where no additives were added to the second dissolution test fluid (pH 6.8), the dissolution rate dropped significantly after 30 minutes. In systems where hydroxypropyl cellulose was added to the test fluid, the final dissolution rate increased slightly, but the dissolution rate dropped rapidly, just as in systems where no additives were added. However, in systems where pregelatinized starch was added to the test fluid, the ability to maintain supersaturation was improved, the time for the dissolution rate to drop was delayed, and the rate of drop in the dissolution rate became significantly slower.
[0100] <Test Example 6: Storage stability of solid dispersion at 40° C. and relative humidity of 75%> SD6 obtained from Production Example 6 was stored at 40°C and 75% relative humidity for 1, 2, and 6 weeks, and the crystal state was confirmed by powder X-ray diffraction measurement. For the measurement, a powder X-ray diffraction device Smart Lab 3kW (manufactured by Rigaku) was used, and the measurement was performed under the following conditions: measurement method: reflection method, filter: Cu K-bate, X-ray output: 40kV, 30mA, measurement range: 2θ=3 to 40deg, scan speed: 8deg / min, step width: 0.02deg. The evaluation criteria and evaluation results of the crystal state are shown in Figure 6.
[0101] A halo pattern was observed for SD6 obtained from Preparation Example 6 at all storage periods, indicating that the enzalutamide in the solid dispersion remained in an amorphous state even after 6 weeks at 40°C and a relative humidity of 75%. EXAMPLES
[0102] Preparation of tablet 5 D-mannitol (manufactured by Freund Corporation: Granutol (registered trademark) S) 13.48 g, light anhydrous silicic acid (manufactured by Freund Corporation: Adsolider (registered trademark) 101) 0.17 g, croscarmellose sodium (manufactured by DuPont Corporation: Ac-Di-Sol (registered trademark) SD-711) 2.68 g, magnesium stearate (manufactured by Taihei Chemical Industry Corporation: magnesium stearate (vegetable)) 0.17 g were mixed to prepare an additive mixture. Enzalutamide 40 mg equivalent (0.20 g) in the solid dispersion SD6 obtained in Production Example 6 and 0.165 g of the additive mixture were weighed out, mixed in a φ9.5 mm mortar, and tableted using a hand press machine at 1 kN to obtain a circular plain tablet (tablet 5) with a tablet mass of 365 mg and φ9.5 mm. EXAMPLES
[0103] Preparation of tablet 6 D-mannitol (manufactured by Freund Corporation: Granutol (registered trademark) S) 13.48 g, light anhydrous silicic acid (manufactured by Freund Corporation: Adsolider (registered trademark) 101) 0.17 g, croscarmellose sodium (manufactured by DuPont Corporation: Ac-Di-Sol (registered trademark) SD-711) 2.68 g, magnesium stearate (manufactured by Taihei Chemical Industry Corporation: magnesium stearate (vegetable)) 0.17 g were mixed to prepare an additive mixture. Enzalutamide 40 mg equivalent amount (0.20 g) in the solid dispersion SD6 obtained in Production Example 6, additive mixture 0.165 g, and pregelatinized starch (manufactured by Matsutani Chemical Industry Co., Ltd.; Matsunolin (registered trademark) SM) 0.04 g were weighed out, mixed in a φ9.5 mm mortar, and tableted using a hand press machine at 1 kN to obtain a circular plain tablet (tablet 6) with a tablet mass of 365 mg and a φ9.5 mm. EXAMPLES
[0104] Preparation of tablet 7 D-mannitol (manufactured by Freund Corporation: Granutol (registered trademark) S) 13.48 g, light anhydrous silicic acid (manufactured by Freund Corporation: Adsolider (registered trademark) 101) 0.17 g, croscarmellose sodium (manufactured by DuPont Corporation: Ac-Di-Sol (registered trademark) SD-711) 2.68 g, magnesium stearate (manufactured by Taihei Chemical Industry Co., Ltd.: magnesium stearate (vegetable)) 0.17 g were mixed to prepare an additive mixture. Enzalutamide 40 mg equivalent amount (0.20 g) in the solid dispersion SD6 obtained in Production Example 6, additive mixture 0.165 g, and pregelatinized starch (manufactured by Matsutani Chemical Industry Co., Ltd.; Matsunolin (registered trademark) SM) 0.08 g were weighed out, mixed in a φ9.5 mm mortar, and tableted with a hand press machine at 1 kN to obtain a circular plain tablet (tablet 7) with a tablet mass of 365 mg and φ9.5 mm.
[0105] The formulations of tablets 5 to 7 produced in Examples 5 to 7 are shown in Table 10.
[0106] [Table 10]
[0107] <Test Example 7: Study on the amount of pregelatinized starch> For tablets 5 to 7, the number of tablets added was 2, and the dissolution test was carried out under the same test conditions as in Test Example 2, and the dissolution rate was calculated. The test results are shown in Table 11 and FIG.
[0108] [Table 11]
[0109] Tablet 5 (enzalutamide: methacrylic acid copolymer LD: copolyvidone = 1:2:2) without added pregelatinized starch did not show the ability to maintain supersaturation, and the dissolution rate decreased after 30 minutes. Tablet 6 (enzalutamide: methacrylic acid copolymer LD: copolyvidone: pregelatinized starch = 1:2:2:1) and tablet 7 (enzalutamide: methacrylic acid copolymer LD: copolyvidone: pregelatinized starch = 1:2:2:2) with added pregelatinized starch showed good ability to maintain supersaturation, and the decrease in dissolution rate was gradual even after 30 minutes, and tablet 7 (enzalutamide: methacrylic acid copolymer LD: copolyvidone: pregelatinized starch = 1:2:2:2) with the highest amount of added pregelatinized starch showed the highest dissolution rate after 3 hours.
[0110] <Production Example 10> Preparation of solid dispersion by spray drying method, Enzalutamide: Methacrylic acid copolymer LD: Copolyvidone = 1:2:2 A solution of 2.0 g of enzalutamide, 4.0 g of copolyvidone (Kollidon (registered trademark) VA64 manufactured by BASF Japan), and 4.0 g of methacrylic acid copolymer LD (Eudragit (registered trademark) L100-55 manufactured by EVONIK Nutrition & Care GmbH) in 90 g of methanol was filtered through a sieve with an opening of 100 μm and spray-dried using a spray dryer (Mini spray dryer B-290 manufactured by Nippon Buchi Co., Ltd., nozzle diameter: 0.7 mm) to obtain a solid dispersion SD10.
[0111] <Production Example 11> Preparation of solid dispersion by spray drying method, Enzalutamide: Methacrylic acid copolymer L: Copolyvidone = 1:2:2 A solution of 2.0 g of enzalutamide, 4.0 g of copolyvidone (manufactured by BASF Japan: Kollidon (registered trademark) VA64), and 4.0 g of methacrylic acid copolymer L (manufactured by EVONIK Nutrition & Care GmbH: Eudragit (registered trademark) L100) dissolved in 90 g of a mixture of acetone / water = 7:3 was filtered through a sieve with an opening of 100 μm and spray-dried using a spray dryer (manufactured by Nippon Buchi; Mini spray dryer B-290, nozzle diameter: 0.7 mm) to obtain solid dispersion SD11.
[0112] After preparing SD10 to SD11, powder X-ray diffraction measurements were performed to obtain the diffraction patterns of each sample. The measurement results are shown in Figure 8. Halo patterns were observed in all the samples prepared.
[0113] Table 12 shows the spray-drying production conditions for solid dispersions SD10 to 11.
[0114] [Table 12] EXAMPLES
[0115] Tablet 8 D-mannitol (Freund Sangyo Co., Ltd.: Granutol (registered trademark) S) 20.0 g, crystalline cellulose (Asahi Kasei Co., Ltd.: Ceolas (registered trademark) UF-702) 6.96 g, light anhydrous silicic acid (Freund Sangyo Co., Ltd.: Adsolider (registered trademark) 101) 0.34 g, croscarmellose sodium (DuPont Co., Ltd.: Ac-Di-Sol (registered trademark) SD-711) 5.36 g, magnesium stearate (Taihei Chemical Industry Co., Ltd.: Magnesium stearate (vegetable)) 0.34 g were mixed to prepare an additive mixture. Enzalutamide 40 mg equivalent (0.20 g) in the solid dispersion SD10 obtained in Production Example 10 and 0.165 g of the additive mixture were weighed out, mixed in a φ9.5 mm mortar, and tableted at 5 kN using a hand press machine. The tableted tablets were pulverized using an agate mortar. 365 mg of the pulverized product was weighed out and compressed into tablets at 2 kN using a hand press in a φ9.5 mm mortar to obtain uncoated tablets of Example 8 (Tablet 8) having a tablet mass of 365 mg and a circular shape of φ9.5 mm. EXAMPLES
[0116] Tablet 9 D-mannitol (Freund Sangyo Co., Ltd.: Granutol (registered trademark) S) 20.0 g, crystalline cellulose (Asahi Kasei Co., Ltd.: Ceolas (registered trademark) UF-702) 6.96 g, light anhydrous silicic acid (Freund Sangyo Co., Ltd.: Adsolider (registered trademark) 101) 0.34 g, croscarmellose sodium (DuPont Co., Ltd.: Ac-Di-Sol (registered trademark) SD-711) 5.36 g, magnesium stearate (Taihei Chemical Industry Co., Ltd.: Magnesium stearate (vegetable)) 0.34 g were mixed to prepare an additive mixture. Enzalutamide 40 mg equivalent (0.20 g) in the solid dispersion SD11 obtained in Production Example 11 and 0.165 g of the additive mixture were weighed out, mixed in a φ9.5 mm mortar, and tableted at 5 kN using a hand press machine. The tableted tablets were pulverized using an agate mortar. 365 mg of the pulverized product was weighed out and compressed into tablets at 2 kN using a hand press in a φ9.5 mm mortar to obtain circular plain tablets of Example 9 (Tablet 9) with a tablet mass of 365 mg and a diameter of φ9.5 mm.
[0117] The formulations of tablets 8 to 9 produced in Examples 8 to 9 are shown in Table 13.
[0118] [Table 13]
[0119] <Test Example 8: Study on combination of solid dispersions and blending amount of copolyvidone> The dissolution test was carried out for tablets 8-9 according to the Japanese Pharmacopoeia Dissolution Test Method, 18th Edition. The tablets were dissolved in a dissolution tester (manufactured by Toyama Sangyo) by the paddle method, the test liquid was 900 mL of dissolution test second liquid (pH 6.8), and the paddle rotation speed was 50 rpm. For the test sample, two tablets (equivalent to 80 mg of enzalutamide) were added and the test was carried out. 15 mL of the dissolution liquid was withdrawn over time from the start of the test until 180 minutes, and immediately 15 mL of the test liquid heated to 37 ± 0.5 ° C was accurately added. The dissolution liquid was filtered through a membrane filter with a pore size of 0.45 μm or less, and the dissolution rate of the filtrate was calculated by liquid chromatography. The ultraviolet absorbance of enzalutamide was measured at 237 nm. The results are shown in Table 14 and Figure 9.
[0120] [Table 14]
[0121] Tablet 8 showed a rapid initial dissolution rate, reaching 85% dissolution rate in 15 minutes. Tablet 9 showed a maximum dissolution rate of just under 50%, but the dissolution rate maintenance time was significantly longer than that of tablet 8.
Claims
1. A tablet comprising a solid dispersion containing enzalutamide and one or more polymers selected from the group consisting of copolyvidone, methacrylic acid copolymer, methylcellulose, and polyvinyl alcohol.
2. 2. The tablet of claim 1, wherein the polymer is a copolyvidone and methacrylic acid copolymer.
3. 2. The tablet of claim 1, wherein the polymers are copolyvidone and methylcellulose.
4. 2. The tablet of claim 1, wherein the polymer is copolyvidone and polyvinyl alcohol.
5. The tablet according to any one of claims 1 to 4, wherein the blending ratio of the polymer is 10.0 to 80.0% by weight based on the total weight of the tablet.
6. The tablet according to any one of claims 1 to 4, wherein the blending ratio of the polymer is 1:0.1 to 1:20, with the blending amount of enzalutamide being 1.
7. 2. The tablet according to claim 1, further comprising pregelatinized starch.
8. The tablet according to claim 7, wherein the blending ratio of the pregelatinized starch is 0.1 to 50.0% by weight based on the total weight of the tablet.
9. 2. The tablet according to claim 1, which is an orally disintegrating tablet.
10. The tablet according to claim 1, which is a film-coated tablet.
11. A method for producing a tablet comprising a solid dispersion containing enzalutamide and one or more polymers selected from the group consisting of copolyvidone, methacrylic acid copolymer, methylcellulose, and polyvinyl alcohol.
Citation Information
Patent Citations
Latent heat exchanger
JP1989004217A
Pharmaceutical composition for oral administration containing enzalutamide
JP7172997B2